2020
DOI: 10.1177/1359105320941217
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and commitment therapy for family caregivers: A systematic review and meta-analysis

Abstract: Acceptance and commitment therapy is an emerging evidenced-based practice, but no systematic review regarding the effects of ACT on family caregivers has been conducted. This article examined the effects of ACT on family caregivers by conducting meta-analysis with a random effects model. Twenty-four articles were identified from four electronic databases searched up to 30 March 2020. Meta-analyses found moderate effects of ACT on depressive symptoms and quality of life, small effects on anxiety, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 50 publications
4
54
0
Order By: Relevance
“…Evidence shows that ACT is effective in improving psychological flexibility and mental health outcomes in clinical and non-clinical youth and adult populations (see the review of meta-analyses, [ 58 ]). In other research, psychological flexibility was also associated with decreases in stress in adult carers [ 60 , 61 ]. A meta-analysis of ACT interventions for adult family carers found that ACT had moderate effects on depression and quality of life, small effects on anxiety, and small to moderate effects on stress [ 61 ].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Evidence shows that ACT is effective in improving psychological flexibility and mental health outcomes in clinical and non-clinical youth and adult populations (see the review of meta-analyses, [ 58 ]). In other research, psychological flexibility was also associated with decreases in stress in adult carers [ 60 , 61 ]. A meta-analysis of ACT interventions for adult family carers found that ACT had moderate effects on depression and quality of life, small effects on anxiety, and small to moderate effects on stress [ 61 ].…”
Section: Discussionmentioning
confidence: 83%
“…In other research, psychological flexibility was also associated with decreases in stress in adult carers [ 60 , 61 ]. A meta-analysis of ACT interventions for adult family carers found that ACT had moderate effects on depression and quality of life, small effects on anxiety, and small to moderate effects on stress [ 61 ]. Public health ACT-based interventions have also been shown to promote mental health in a variety of youth populations [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ] using flexible modes of delivery: youth in the general population via group delivery [ 59 , 63 , 64 , 66 ], and university students via online delivery [ 65 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…An approach consistent with these treatment strategies is acceptance and commitment therapy (ACT), which offers a wide range of tools and practices to work with EA, offering acceptance-based coping strategies to handle suppression and assists family caregivers in identifying their true values and devoting more time for themselves instead of focusing only on their caregiving role. Indeed, studies suggest that ACT with family caregivers is effective for the treatment of depression and anxiety, and well-received by the family caregivers (Han et al, 2021;Losada et al, 2015;Marquez-Gonzalez et al, 2020). As we are faced with increasing numbers of older adults and family caregivers, it is essential that health professionals and other groups working with family caregivers are educated about both core processes of change and the adverse effects of avoidant coping strategies on psychological well-being and quality of life in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis by Collins and Kishita (2019) revealed that mindfulness and acceptance-based interventions, including ACT, were largely effective at reducing symptoms of depression in dementia caregivers. In addition, Han, Yuen, and Jenkins (2021) investigated the effects of ACT on caregivers of children and found moderate effects on depressive symptoms and quality of life. However, ACT intended for the sole use of older family caregivers is rare.…”
Section: Introductionmentioning
confidence: 99%